2005
DOI: 10.1128/mcb.25.20.9092-9102.2005
|View full text |Cite
|
Sign up to set email alerts
|

Targets of the Gal4 Transcription Activator in Functional Transcription Complexes

Abstract: Although biochemical and genetic methods have detected many activator-transcription factor interactions, the direct functional targets of most activators remain undetermined. For this study, photo-cross-linkers positioned within the Gal4 C-terminal acidic activating region were used to identify polypeptides in close physical proximity to Gal4 during transcription activation in vitro. Of six specifically cross-linked polypeptides, three (Tra1, Taf12, and Gal11) are subunits of four complexes (SAGA, Mediator, Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 53 publications
4
110
0
2
Order By: Relevance
“…In general, these targets are located in coactivator complexes and chromatin-remodeling or -modifying factors rather than in subunits of the general transcription factors. For example, protein crosslinkers positioned within the activation domains of Gcn4 and Gal4 have conclusively identified three common activator targets (Gal11, Tra1, and Taf12) that are subunits of four coactivator complexes (Mediator, SAGA, NuA4, and TFIID) (Fishburn et al 2005;Reeves and Hahn 2005;Herbig et al 2010). The activator-Tra1 interaction was also revealed by in vivo FRET analysis (Bhaumik et al 2004) and by in vitro interaction and functional studies in vivo (Brown et al 2001).…”
Section: Activator Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these targets are located in coactivator complexes and chromatin-remodeling or -modifying factors rather than in subunits of the general transcription factors. For example, protein crosslinkers positioned within the activation domains of Gcn4 and Gal4 have conclusively identified three common activator targets (Gal11, Tra1, and Taf12) that are subunits of four coactivator complexes (Mediator, SAGA, NuA4, and TFIID) (Fishburn et al 2005;Reeves and Hahn 2005;Herbig et al 2010). The activator-Tra1 interaction was also revealed by in vivo FRET analysis (Bhaumik et al 2004) and by in vitro interaction and functional studies in vivo (Brown et al 2001).…”
Section: Activator Targetsmentioning
confidence: 99%
“…Tra1 and its human homolog, TRRAP, are members of the PI3-related protein kinase family, but Tra1 and TRRAP have specifically lost kinase activity (Mutiu et al 2007). Biochemical and genetic experiments showed that several activators, including Gcn4 and Gal4, interact with Tra1 and that this interaction is important for activated transcription of SAGAdependent genes (Brown et al 2001;Fishburn et al 2005;Reeves and Hahn 2005). Tra1 is also likely responsible for activator recruitment of the NuA4 coactivator.…”
Section: Tra1 Has Multiple Functions Within Saga and Nua4mentioning
confidence: 99%
“…Studies in different eukaryotes have suggested that the presence of SAGA at the promoters of genes is needed to facilitate Pol II recruitment and pre‐initiation complex (PIC) formation (Wyce et al , 2007; Nagy et al , 2009; Helmlinger et al , 2011; Lang et al , 2011). The recruitment of SAGA and ATAC coactivator complexes to genomic loci has been suggested to take place by several distinct mechanisms: (i) by activator mediated recruitment (McMahon et al , 1998; Brown et al , 2001; Fishburn et al , 2005; Reeves & Hahn, 2005), (ii) by interactions with basal transcription machinery components (Larschan & Winston, 2001; Laprade et al , 2007; Mohibullah & Hahn, 2008) and (iii) through chromatin‐interacting domains of SAGA and ATAC subunits (Hassan et al , 2002; Vermeulen et al , 2010; Bian et al , 2011; Bonnet et al , 2014). Nevertheless, the dynamics of SAGA and ATAC interactions with chromatin are not yet well understood, as there has been no direct and systematic monitoring of the nuclear mobility of these two co‐activator complexes in live cells.…”
Section: Introductionmentioning
confidence: 99%
“…One well-characterized MDT-15 ortholog is yeast GAL11, which is a direct target of the regulatory factors GAL4 and GCN4 (Fishburn et al 2005;Reeves and Hahn 2005); interestingly, ⌬gal11 cells express GCN4 targets normally, but are defective in expression of GAL4 targets. Consistent with this, GCN4 and GAL4 recruit multiple regulatory complexes to achieve activated transcription (Bryant and Ptashne 2003;Govind et al 2005).…”
Section: Mdt-15 May Participate In Multiple Signal Transduction Cascadesmentioning
confidence: 99%